Urgensi Pengembangan Ilmu Hukum dalam Masyarakat Ekonomi Asean 2015 - Lasmana, Lanny; Haykal, Hassanain (Zenit, 2014)
The realization of AFTA in 2015 is a milestone of competition in trades and goods in ASEAN countries. Indonesia as one of the ASEAN countries that approves of AFTA realization will face morecompetetive market demands. Various preparations are done in all aspects of this nation. One of the aspects to be well managed is law which develops and undergoes changes. The flow of goods and services, as well as cultures from other AFTA countries have caused dynamic changes in law.Professional in legal field are necessary to solve all kinds of problems. To produce professionals in the field of law, holistic development is necessary in education, especially in Law Higher Education, which includes study methods, curricula and law education itself. The law education as one of the various branches of science is an important foundation in law education as well as legal systems in Indonesia. The law education that can face community’s dynamic development is the one that notonly emphasizes on theoretical aspect, but also on practical aspects that can give a clearer and concrete picture of the matters. In its development, law education can be directed to a more constructive, structured, dynamic science, and produce professionals with competence and integrity. In addition, law education is expected to be able to create justice and law assurance to solve legal matters dynamically after the foundation of AFTA.Keywords: Law Education, Asean Economy Community